The fish industry in Eritrea: from comparative to competitive advantage - Teweldemedhin, M. Y (Advances in Aquaculture and Fisheries Management, 2016)
The paper examines the main constrains in stimulating extent of production driven supply chains, that could able to transform into market driven supply chain management.; Questionnaires, were developed and administered to marketing agents using purposive sampling, with the application of Porter’s diamond of national competitive advantage. Red sea being underexploited resource; and it is unique opportunity for the development of the country (MOF, 1997) . However, this comparative advantage has never been converted to competitive advantage. Comparing to the percentage of fish population with in 100km from the coastal, Eritrea has the larger fish resource concentration in the region (73%). However, the sector has never made significant contribution to the country food security. The study confirms that all the role payers in the fish market chain and policy makers need to take a strategic approach, in identifying target markets, and ways to build strong and sustainable production. Moreover, all stack holder in the sector needs to formulate how to move up to: the value chain; niche marketing opportunity; converting comparative into competitive advantage; specifically focus on the services revolution; and overcoming technical and structural barriers.